The importance of taking into consideration the integration between the components of human resources development system and the demographic dimension in Sudan - Abu Zeid, Mu'tasim Hussein (Journal of Economic, Administrative and Legal Sciences, 2017)
This study attempted to identify the importance of integration and interdependence in human resources development programs and taking into account the importance of the population dimension when establishing the aspects of the intellectual aspect in the development of human resources, which means the system from which the psychological and behavioral aspects and economic aspects can be built. A model of human resources development programs, highlighting the demographic factors and identifying the views of a group of professional actors in the fields related to the field of human resources development, and through the descriptive approach, the study reached many The results and recommendations that contribute to the addition and search for solutions to many issues both at the community level and at the level of organizations related to human resources development.